"Taking Up a New Problem": Context and Determinants of Pod-Mod Electronic Cigarette Use Among College Students. (March 2021) - Kava, Christine M.; Soule, Eric K.; Seegmiller, Laura; Gold, Emily; Snipes, William; Westfield, Taya; Wick, Noah; Afifi, Rima
In this article, we explore the context and determinants of pod-mod electronic cigarette (ECIG) use among college students aged 18 to 24 in the United States. We conducted semi-structured interviews with 55 students ( M age = 20 years, 56% female, 65% White) on three campuses in the Northwest, Midwest, and Southeast. We performed a thematic analysis. Students described ECIG use by peers, increased ECIG exposure and prevalence in college, and school-related stress as reasons for vaping. Pod-mod features such as convenience, design, easy concealment, and flavors made vaping more appealing. Negative aspects of vaping included addiction, cost, and possible health consequences. Most viewed vaping as a college behavior and intended to quit after graduation. Our results show that the college environment plays a major role in young adult ECIG use. These findings can inform the development of targeted interventions to prevent and control uptake of ECIGs by young adults.